Nicht genutzte Chancen der Föderalismusreform - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2006)
The reform of German federalism was meant to overcome the mutually imposed constraints on autonomous political action at the federal and Land levels. The proposals that are now to be discussed in parliament will provide some improvement, but are far from adequate in light of the original goals or the practical needs for reform. The reason was a simplistic approach to reform which, if it had been realized, would have violated the normative requirements of interregional equality. Options which could have increased autonomy without violating egalitarian standards were ignored in the process. – – Die Föderalismusreform sollte die wechselseitige Lähmung der Politik in Bund und Ländern überwinden. Die jetzt auf den parlamentarischen Weg gebrachten Vorschläge bringen manche Verbesserungen, bleiben aber weit hinter dem ursprünglichen Ziel und dem sachlich Notwendigen zurück. Der Grund liegt in einem zu einfachen Reformkonzept, das - wenn es denn verwirklicht worden wäre - den normativen Anspruch auf gleichwertige Lebensverhältnisse in ungleichen Ländern hätte verletzen müssen. Dagegen wurden Reformoptionen ignoriert, die eine höhere Autonomie der Landes- und Bundespolitik ermöglicht hätten, ohne diesen Anspruch zu verletzen.
Keywords: 300